Time Preference Instability, Financial and Working Status - Caterina Giannetti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
In this paper we study the drivers of change in individuals' discount rates. Our panel dataset allows us to jointly consider socio-demographics, financial status and literacy, as well as job characteristics among the possible determinants. Our results suggest that individual time-preferences are not stable over time, especially among individuals who hold debts. Labour market variables do not play any direct role. A large part of the variation, however, is not explained by none these drivers. This supports the view that discount rates are related to an underlying unobservable individual trait.
Keywords: C33; D1; D90; 330